2014
DOI: 10.1007/s10661-014-4042-9
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residue analysis of soil, water, and grain of IPM basmati rice

Abstract: The main aim of the present investigations was to compare the pesticide load in integrated pest management (IPM) with non-IPM crops of rice fields. The harvest samples of Basmati rice grain, soil, and irrigation water, from IPM and non-IPM field trials, at villages in northern India, were analyzed using multi-pesticide residue method. The field experiments were conducted for three consecutive years (2008-2011) for the successful validation of the modules, synthesized for Basmati rice, at these locations. Resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…This result agrees with earlier studies, which found that pestmanagement systems that fail to use IPM strategies have lower average rice yields (Sattar et al, 2004;Alam, 2013). Pest-control strategies that include appropriate pesticide use have consistently been shown to increase rice production (Arora et al, 2014;Muck, 2015). Jacobsen and Hjelmso (2014) report that heavy pesticide use often has a higher cost-to-yield ratio than IPM methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agrees with earlier studies, which found that pestmanagement systems that fail to use IPM strategies have lower average rice yields (Sattar et al, 2004;Alam, 2013). Pest-control strategies that include appropriate pesticide use have consistently been shown to increase rice production (Arora et al, 2014;Muck, 2015). Jacobsen and Hjelmso (2014) report that heavy pesticide use often has a higher cost-to-yield ratio than IPM methods.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, chemical pesticides have played a vital role in providing an abundant and inexpensive food source (US-EPA, 2015 3 ). Despite an increase in food production, however, the persistent overuse of chemicals has resulted in a number of adverse environmental impacts such as, outbreak of secondary pests, decreasing of beneficial insects and the accumulation of toxins in the food webs (Arora et al, 2014). Continued research and development of sustainable and effective agricultural-pestmanagement techniques is essential if farmers are going to successfully adopt environmentally friendly pest-management strategies (Pretty and Bharucha, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides compatible with IPM strategies have been shown to be beneficial for the control of rice pests during the germination, tillering, vegetative growth, and flowering [54]. IPM strategies that employ appropriate pesticide use have consistently been shown to increase rice production [21,55].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding this, at a community level worldwide, chemical pesticides have played a vital role in providing an abundant and inexpensive food source [20]. Despite this, the persistent use and overuse of chemicals in non-IPM treated farming systems have resulted in a number of adverse environmental problems [21]. For local farmers, continuing education and training play a vital role in advancing their knowledge of IPM practices and the adverse impacts agrochemicals can have on the rice ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Difenoconazole residues had been analyzed in apple utilizing gas chromatography (GC) (Guo, Li, Gao, & Wang, ), in rice plants using GC coupled with a mass selective detector (Wang, Wu, & Zhang, ), in tomato using ultra‐performance liquid chromatography coupled with tandem mass spectrometry (UPLC–MS/MS; Kong et al, ) and in onion using liquid chromatography coupled with electrospray ionization tandem mass spectrometry (LC‐ESI‐MS/MS) (Rodrigues et al, ). Propiconazole residues were analyzed in peppermint leaf, oil and spent grain utilizing gas chromatography with mass spectrometry (GC–MS; Garland, Menary, & Davies, ; Navarro, Pérez, Vela, Mena, & Navarro, ), in boronia using GC with high‐resolution mass spectrometry (Garland, Davies, & Menary, ) and in rice with other pesticides using gas–liquid chromatography with electron capture detection (Arora, Mukherji, Kumar, & Tanwar, ). Pyraclostrobin residues were analyzed in vines utilizing liquid chromatography with mass spectrometry (LC–MS; Garau et al, ), in grapes using GC–MS (Lagunas‐Allué, Sanz‐Asensio, & Martínez‐Soria, ) and in peanuts using a modified Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) ‐ LC–MS/MS method (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%